(untitled) (Palíndromo, 2024)
In this paper we will present a series of paintings idealized by Pedro Americo about the Minas Gerais Conspiracy. The artist produced the paintings between 1892 and 1893, but only the canvas Tiradentes Esquartejado was completed. The series of five canvases recalls the structure of a tragedy: happiness, error and catastrophe, in a cause-and-effect relationship. Gonzaga is happy in anticipation of the wedding while embroidering his fiancée's wedding dress; Tiradentes, gathered with other fellow conspirators while he makes a mistake by trusting them more than he should; and the catastrophic reaction to the movement, exemplified by the suicide/murder of Claudio Manuel da Costa and the dismemberment of Tiradentes. The tragic structure shows how the painter saw the conspiracy as a fragile movement, doomed from the start.